PENGARUH PADAT PENEBARAN TERHADAP PERTUMBUHAN DAN KELULUSHIDUPAN BENIH IKAN KERAPU BEBEK (CROMILEPTES ALTIVELES) STADIA D60-D120 - Luky Mudiarti; Nurcahyo Kursistyanto; Noor Nailie Azzat; Budi Lofian (Jurnal Disprotek, 2023)
Humback Grouper (Cromileptes altiveles) is a type of grouper fish that has high economic value. Currently the problem faced in grouper farming is the low survival rate due to cannibalism. This study aims to determine the effect of stocking density on the growth and survival of  Humback    Grouper (Cromileptes altiveles) seeds from stages D60–D120. This study used a completely randomized design with four treatments at densities of 2 individuals/10 liters, 4 individuals/10 liters, 6 individuals/10 liters, and 8 fish/10 liters repeated for each treatment three times. The feed was given in the form of chopped trash fish with a frequency of twice a day in the morning and evening. Growth data (absolute growth data, daily growth data) and survival data were analyzed using analysis of variance (ANOVA) to show that the treatment had an effect on growth and Humback  Grouper (Cromileptes altiveles) survival rate and Duncan's  test to find out the difference in mean values between treatments. The results showed that stocking density had a very significant effect on absolute growth and daily growth rate, and had a significant effect on survival. Treatment A (2 fish/10 liters) produced the best absolute growth, daily growth rate, and survival with values of 20.047 g, 3.303%/day, 100%, respectively.